“Tornar-me branca, tornar-se branca”: narrativas de psicólogas brancas sobre as relações raciais, um diálogo a partir da branquitude crítica - Carvalho, Sara Moura de (2020)
In the last two decades, research and professional practices in psychology have been reviewed in new political, economic, social and cultural contexts in the country, demonstrating that this science constitutes a fertile field of productions that can both compact and break with the field's epistemological traditions. Among the critical approaches, those that investigate race relations in the practices of psychology are perhaps those that have produced the greatest theoretical and conceptual challenges. This research has as main objective to understand, through the autobiographical narrative investigation tool (history and life project), the narratives of psychologists, who call themselves white, as they perceive the theme of race relations, as well as, to apprehend the meanings and meanings that they attribute to their social identities, above all, racial. Five psychologists, all born and / or working in the state of São Paulo, narrated their trajectory with the theme, as well as the possible meanings about their racial identities. The results of the narratives showed that they were more sensitive to the theme from interracial contact, as well as from awareness-raising practices with the theme. The analysis of the data will be through the meaning cores. The selection criterion for participation in the research was that they were trained in psychology, self-declared to be white and had some kind of approximation to the theme of race relations, obtaining as a proposal, a critical look at whiteness and reflection on the possibilities to expand and / or reflect on practices involved with the Brazilian racial context. This work arose with the intention of pointing out the importance of articulating race relations in the practice of white psychologists. In this sense, we sought to verify how the implications of brachitude can unfold in the psi performance - with this, the critical studies of whiteness helped for the theoretical contribution, as well as the sociological studies on race and racism. The foundations of social psychology and the decolonial perspective were based on the stitching of the outlined dialogues